DNA barcoding, phylogenetic analysis and secondary structure predictions of Nepenthes ampullaria, Nepenthes gracilis and Nepenthes rafflesiana - Saidon, Nur Azreen (MDPI, 2023)
Nepentheceae, the most prominent carnivorous family in the Caryophyllales order, comprises the Nepenthes genus, which has modified leaf trap characteristics. Although most Nepenthes species have unique morphologies, their vegetative stages are identical, making identification based on morphology difficult. DNA barcoding is seen as a potential tool for plant identification, with small DNA segments amplified for species identification. In this study, three barcode loci, ribulose-bisphosphate carboxylase (rbcL), intergenic spacer 1 (ITS1) and intergenic spacer 2 (ITS2) and the usefulness of the ITS1 and ITS2 secondary structure for the molecular identification of Nepenthes species were investigated. An analysis of barcodes was conducted using BLASTn, pairwise genetic distance and diversity, followed by secondary structure prediction. The findings reveal that PCR and sequencing were both 100% successful. The present study showed the successful amplification of all targeted DNA barcodes at different sizes. Among the three barcodes, rbcL was the least efficient as a DNA barcode compared to ITS1 and ITS2. The ITS1 nucleotide analysis revealed that the ITS1 barcode had more variations compared to ITS2. The mean genetic distance (K2P) between them was higher for interspecies compared to intraspecies. The results showed that the DNA barcoding gap existed among Nepenthes species, and differences in the secondary structure distinguish the Nepenthes. The secondary structure generated in this study was found to successfully discriminate between the Nepenthes species, leading to enhanced resolutions.